1994
DOI: 10.1093/ndt/9.5.539
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of fungal peritonitis complicating continuous ambulatory peritoneal dialysis with oral fluconazole: a series of 21 patients

Abstract: Twenty-one episodes of fungal peritonitis occurred over 35 months among 290 patients on CAPD, accounting for 6.3% of all peritonitis episodes. Patients with more frequent bacterial peritonitis were at higher risk of developing fungal peritonitis, and 28.6% of cases followed antimicrobial therapy. Candida species accounted for 85.7% of cases. Oral fluconazole was used as initial therapy in all patients, which was followed by catheter removal if peritonitis failed to improve. The cure rate with fluconazole thera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
62
2

Year Published

1998
1998
2011
2011

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(67 citation statements)
references
References 0 publications
3
62
2
Order By: Relevance
“…Several studies have shown that fluconazole monotherapy is effective and reaches good plasma and dialysate concentrations when given orally [22][23][24] as well as intraperitoneally [22,25,26]. Chen et al [27] recently compared oral fluconazole monotherapy with either amphotericin B intraperitoneally or amphotericin B intraperitoneally combined with fluconazole orally or intravenously.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that fluconazole monotherapy is effective and reaches good plasma and dialysate concentrations when given orally [22][23][24] as well as intraperitoneally [22,25,26]. Chen et al [27] recently compared oral fluconazole monotherapy with either amphotericin B intraperitoneally or amphotericin B intraperitoneally combined with fluconazole orally or intravenously.…”
Section: Discussionmentioning
confidence: 99%
“…42,43 Incidence ranges between 0.5-1.4 episodes per patient per year, 44 with about 60% of patients developing peritoneal dialysis peritonitis in the first year. 45 At least a quarter will culminate in catheter failure.…”
Section: Peritoneal Dialysis Peritonitismentioning
confidence: 99%
“…Recent reports on fungal peritonitis in children receiving peritoneal dialysis have indicated the usefulness of vigorous peritoneal lavage through the catheter [17,18]; however, its overall efficacy is still controversial, because it delays the timing of catheter removal [19]. Furthermore, after catheter removal alone, or with antifungal therapy, the signs and symptoms of fungal peritonitis may remain for more than 7 days [20][21][22]. In our case, however, the systemic inflammatory findings rapidly returned to normal ranges after surgery (Fig.…”
Section: Discussionmentioning
confidence: 99%